Results From the Partnership for Advancement in Neuromodulation Registry: A 24‐Month Follow‐Up. Issue 2 (February 2016) - Deer, Timothy; Skaribas, Ioannis; McJunkin, Tory; Nelson, Christopher; Salmon, John; Darnule, Amit; Braswell, John; Russo, Marc; Fernando Gomezese, Omar
Abstract : Objective: This longitudinal, clinical outcome study was a multicenter, prospective, observational, registry with a 24‐month assessment of patients implanted with spinal cord stimulation (SCS) systems for the management of chronic pain of the trunk and/or limbs. Methods: On informed consent and institutional review board approval, 614 patients from 39 sites were enrolled within 30 days following permanent SCS system implantation. Medication usage, patient‐reported pain relief (PRP), categorical ratings of pain relief, pain disability index scores (PDI), quality of life (QoL), and patient satisfaction were assessed at enrollment, 3‐, 6‐, 12‐, 18‐, and 24‐month postimplant. Device‐related adverse events (AEs) were recorded and reported. Results: Across all visits, statistically significant improvements were reported on all outcome measures. Mean PRP was 58.5% (± 26.4) at 3 months, 56.8% (± 29.2) at 6 months, 57.7% (± 28.9) at 12 months, 55.6% (± 29.8) at 18 months, and 56.3% (± 30.3) at 24 months. More than 65% of patients at any visit reported a PRP ≥ 50%. Mean PDI scores reduced from 46.9 points at baseline to 32.7, 31.8, 31.5, 32.1, 32.1 points at 3, 6, 12, 18, and 24 months ( p ≤ 0.0001), respectively. Greater than 76% of patients at any visit were satisfied with their therapy. The majority of patients categorized pain relief as excellent or good on a 5‐item scale and reported overall QoL as greatly improved or improved on a 5‐item scale. An average of 88% of patients stopped, decreased, or did not change dose of narcotics/opioids. The most common AE was diminished or loss of pain relief in 11.4% of enrolled patients. Conclusions: Most patients experienced substantial pain relief and a significant improvement in all outcome measures. These results further support the safety, efficacy, and sustainability of SCS in clinical practice.